PERLINDUNGAN KONSUMEN DALAM ERA DIGITAL: KAJIAN TERHADAP KEBIJAKAN HUKUM DI INDONESIA - Purnomo, Maharani Aprilia Putri (Ensiklopedia Education Review, 2025)
Abstract: The digital era has brought about significant transformations in economic transactions, marked by a substantial increase in electronic commerce (E-commerce). However, this development also presents new challenges related to consumer protection, particularly in aspects such as personal data security, information transparency, and problem solving. This journal the legal policies in Indonesia that aim to ensure consumer protection in digital era. Using a normative approach and analyzing legislation such as the consumer protection law, the Electronic Information and Transactions Law (ITE Law), and government regulations related to personal data protections, but there are still various weaknesses in its implementation. There is a need for harmonization of policies and strengthening of law enforcement to optimally safeguard consumer rights. Keywords : Consumer Protections, Legal Policy, E-commerce.